Evalution of Hridya Mahakashaya of Charak Samhita in CVS :- A Literary Review - Chaudhary, Kiran; Kaushal, Kamini; Kaswan, Sushil Kumar (International Research Journal of Ayurveda & Yoga, 2022)
Hridya Mahakashaya denotes group of ten medicines, Which act on cardiovascular diseases . Hridya Mahakashaya is the 10th gana of the 50 Mahakashaya gana described in fourth chapter of Sutra Sthana of Charak Samhita and includes Amra, Amratak , Lakuch , Karmarda , Virkshamla, Amlavetas, Kuval, Badar, Dadim , Matulunga ten ingredients. These 10 plants are work together and give enhanced effect . They are also effective individually . All ten drugs are Amla Rasa pradhana sour in test and rich source of vitamin c. Vitamin c is proved to be a potent Antioxidant as well as a good stress buster. These plants having Amla , Madhura Ras , Guru ,Ruksha guna , Ushana Virya , Amla Vipaka and Tridoshaghan properties.